Magnesium and the Problem of Design in Your Product - Dow Chemical Company (1951)
Black and white print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. Includes a description of a manufacturing scenario in which the use of Dowmetal magnesium material eases re-design considerations. The material is advertised as lightweight, strong, corrosion-resistant, and able to be shaped and produced in a variety of forms. Depicts a hand holding a design compass. Includes a brief description of Dowmetal's application to the United States' defense effort. The Dowmetal logo, a hand holding a winged ingot of magnesium, is located in the bottom right of the advertisement. Found on page 109 of Time Magazine, October 8, 1951 issue.
Keywords: Advertising; Dow Chemical Company; Advertising, Industrial; Chemical Industry; Magnesium alloys; Mineral industries